Role of entrepreneurial competence, entrepreneurial education, family support and entrepreneurship policy in forming entrepreneurial intention and entrepreneurial decision - Quang Hieu Le; Nguyen Thi Loan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
This study proposes specific solutions to promote entrepreneurial intention and encourages converting entrepreneurial intention into entrepreneurial decisions in the future. In recent years in Vietnam, many studies have been conducted to find solutions to promote, encourage, and motivate young people in general and students, in particular, to participate in entrepreneurship to meet up the goal of 2.0 million enterprises by 2030 as a driving force to promote economic development. For the same purpose, the paper uses AMOS software with the SEM structure model and a sample size of 432 graduated students in business, financial and technical universities in Vietnam to clarify the relationship between the factors of entrepreneurial competence and education, family support, and entrepreneurship policy on the process of forming the entrepreneurial intention and entrepreneurial decision. The study concludes that entrepreneurial competence, entrepreneurial education, and family support have positive effect on entrepreneurial intention and finally entrepreneurial intention has a positive effect on entrepreneurial decision.
Keywords: 330; entrepreneurial competence; entrepreneurial education; family support; entrepreneurial policy; entrepreneurial intention; entrepreneurial decision; family background